Electrocatalysis of Direct Methanol Fuel Cells 2009
DOI: 10.1002/9783527627707.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube‐Supported Catalysts for the Direct Methanol Fuel Cell

Abstract: Fuel cells generate power by converting chemical energy to electricity via electrochemical reactions, which involve eco-friendly reactants and products, in comparison to conventional power generators based on the internal combustion engine. Accordingly, the fuel cell is an attractive and promising power generator with a wide range of applications in sensors, portable devices, automotives, and stationary power systems. The direct methanol fuel cell (DMFC) resembles the proton exchange membrane fuel cell (PEMFC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
1
0
0
Order By: Relevance
“…8 shows the linear cyclic voltammeter of the electrodes at different graphite ratio.At room temperature, the air flow maintains 40 ml/min. The test results show that the reduction peak is found in each electrode testing,and the linear sweep curves are similar with the curve found in the oxygen reduction process at platium catalyst in several reports [14,15] . So it is found that the tubular electrode with high porosity and low resistance has a high electrical performance.…”
Section: Ratio Of Graphite( %)supporting
confidence: 85%
“…8 shows the linear cyclic voltammeter of the electrodes at different graphite ratio.At room temperature, the air flow maintains 40 ml/min. The test results show that the reduction peak is found in each electrode testing,and the linear sweep curves are similar with the curve found in the oxygen reduction process at platium catalyst in several reports [14,15] . So it is found that the tubular electrode with high porosity and low resistance has a high electrical performance.…”
Section: Ratio Of Graphite( %)supporting
confidence: 85%